2018
DOI: 10.1111/ijcp.13287
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation, perceived disability, hopelessness and affective temperaments in patients affected by Parkinson's disease

Abstract: Summary Background Previous studies investigating the risk of suicide in patients with Parkinson's disease (PD) have reported conflicting results. This study evaluated suicide risk in PD and investigated the relationship between suicide risk and perceived disability, hopelessness and affective temperaments in PD. Methods One‐hundred and twenty PD patients were consecutively enrolled. The diagnosis of PD was based on clinical criteria. All patients underwent a psychiatric evaluation that included the administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
9
1
Order By: Relevance
“…The other 4 studies were performed in England [ 18 ], South Korea [ 19 ], Denmark [ 17 ], and Serbia [ 20 ], and it is reasonable to speculate an increased risk of suicide and/or suicidal ideation in PD patients. Similarly, when combining the ORs of studies comparing suicide risk between PD patients and nongeneral population controls (healthy controls or patients with psoriasis or glaucoma) [ 15 , 16 ], we also found a significantly increased risk of suicide in PD patients, supporting our speculation that PD may increase risk of suicide or suicidal ideation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The other 4 studies were performed in England [ 18 ], South Korea [ 19 ], Denmark [ 17 ], and Serbia [ 20 ], and it is reasonable to speculate an increased risk of suicide and/or suicidal ideation in PD patients. Similarly, when combining the ORs of studies comparing suicide risk between PD patients and nongeneral population controls (healthy controls or patients with psoriasis or glaucoma) [ 15 , 16 ], we also found a significantly increased risk of suicide in PD patients, supporting our speculation that PD may increase risk of suicide or suicidal ideation.…”
Section: Discussionsupporting
confidence: 83%
“…In PD patients, non-motor symptoms including anxiety, depression, sleep disorder, cognitive impairment, and hyposmia are common [ 28 ], and these non-motor symptoms severely affect patients' quality of life, could lead to frailty and hopelessness, and finally may cause suicide [ 15 ]. Additionally, it has been reported that suicide risk in PD patients could be related to the frequency of motor symptoms, severity of non-motor symptoms, and patients' personal acceptance of PD-induced disability [ 16 ]. Among all these factors, depression is most recognized [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fa that SA and completed suicide rates in PD are still controversial, being either higher or lower than that of the general population as shown in different studies (for a recent systematic review, see Berardelli et al [ 20 ]), one unequivocal factor is the severity of the concomitant depressive symptomatology including an increase of SI [ 20 , 21 ]. In different studies, death ideation rates have ranged from 21-28.4% and of SI from 9-14% [ 20 , 21 ]. SI has shown to be associated with increased perceived disability, with hopelessness as a risk factor [ 21 ].…”
Section: Reflections Regarding Suicidality In Neurological Diseases Amentioning
confidence: 99%
“…In different studies, death ideation rates have ranged from 21-28.4% and of SI from 9-14% [ 20 , 21 ]. SI has shown to be associated with increased perceived disability, with hopelessness as a risk factor [ 21 ]. Increased SB risk in PD has also been associated with iatrogenic psychotic symptoms and impulse dyscontrol.…”
Section: Reflections Regarding Suicidality In Neurological Diseases Amentioning
confidence: 99%
“…An association between neurologic diseases and SI, SA, and SB was observed ( 6 , 12 , 51 55 ), especially for stroke and hemiplegia ( 4 , 11 , 13 , 56 , 57 ), epilepsy ( 4 , 8 , 45 , 58 ), and dementia ( 13 , 59 , 60 ). A greater rate of SI was documented in patients with Parkinson’s disease ( 60 , 61 ), and the role of sub-thalamic deep brain stimulation (DBS) on suicidality risk in patients treated for extrapyramidal movement disorders is still discussed [for a recent systematic review, see ( 62 )]. The pain was significantly and independently associated with SI/wishes to die ( 21 , 22 , 63 66 ) and completed suicides ( 8 , 10 , 17 ).…”
Section: Discussionmentioning
confidence: 99%